2013
DOI: 10.1309/ajcptma1f6lwytqv
|View full text |Cite
|
Sign up to set email alerts
|

Software-Automated Counting of Ki-67 Proliferation Index Correlates With Pathologic Grade and Disease Progression of Follicular Lymphomas

Abstract: Objectives To examine the accuracy of software-assisted measurement of the Ki-67 proliferation index (PI) and its correlation with the grade and clinical progression of follicular lymphoma (FL). Methods High-power field equivalents were extracted from H&E- and Ki-67–immunostained slides of FL, and a nuclear quantitation algorithm was used to calculate a PI. Representative fields were manually counted for validation with close agreement. Results The PI was significantly higher in World Health Organization g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Noticeably, 12 different biological processes were significantly different between the studied FL groups, with cell cycle (higher in FL3B/DLBCL) and signal transduction (higher in FL1‐3A) reaching the highest statistical significance (Fig ) (Table SVII). Interestingly, cell proliferation is a relevant deregulated process with clinical impact in FL (Janikova et al , ; Samols et al , ; Kedmi et al , ). Our results suggested that changes in lncRNA expression between FL histological subgroups could contribute in part to the differential biological and clinical features by modulating the expression of proliferation‐related genes.…”
Section: Resultsmentioning
confidence: 99%
“…Noticeably, 12 different biological processes were significantly different between the studied FL groups, with cell cycle (higher in FL3B/DLBCL) and signal transduction (higher in FL1‐3A) reaching the highest statistical significance (Fig ) (Table SVII). Interestingly, cell proliferation is a relevant deregulated process with clinical impact in FL (Janikova et al , ; Samols et al , ; Kedmi et al , ). Our results suggested that changes in lncRNA expression between FL histological subgroups could contribute in part to the differential biological and clinical features by modulating the expression of proliferation‐related genes.…”
Section: Resultsmentioning
confidence: 99%
“…HIF-1α, VEGF, γ-H2A.X, annexin V, caspase-3, GAPDH, MCT4, LDH positivity was evaluated in the whole tumor area. The Aperio nuclear V9 algorithm was used to quantitatively identify Ki-67-positive cells as previously described (33, 37). …”
Section: Methodsmentioning
confidence: 99%
“…The authors also noted that digitally-obtained MIB-1 indices might correlate better with clinical outcome than the manually-counted value, but that further studies with larger sample sizes will be necessary to ascertain this. Notably, a recent study by Samols et al [4] examining follicular lymphoma showed that although a higher proliferative index in general correlated with a higher histologic grade, the authors identified a subset of low grade follicular lymphoma with a high proliferative index, a finding which itself had been previously reported by Wang et al (2005) [16]. This cohort reportedly showed a shorter overall survival, and Samols et al suggested that they should be considered as a different prognostic group compared with patients with follicular lymphoma whose proliferative fraction is low.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, automated image analysis has the potential to yield continuous variable data, unlike semi-quantitative analysis, which typically furnishes data in discrete increments. Many studies have shown digital quantification methods to demonstrate comparable accuracy to carefully performed formal manual quantification [4,9,10]. In this way, quantitative image analysis has the potential to objectively, accurately and consistently provide biomarker labelling indices, both in research and clinical settings [11].…”
Section: Journal Of Histology and Histopathology Issn 2055-091x | Volummentioning
confidence: 99%
See 1 more Smart Citation